Migration of digital content and provision of viable platform for effective library operations: the millennium experiences of two academic libraries In Nigeria (2014)
As the number of internet users and searchable content is increasing day by day, the text and documents become more complex and are becoming more difficult to find and investigate. Efficient search and retrieval of the required information is very critical for the internet users which is becoming a challenge day by day. In this paper we present an ontological model for efficient text-based search functionality. The goal is to let the user explore all available options to find and retrieve the required piece of information. The ontological model is presented for a university website as a case study and some usage scenarios are given.